2005
DOI: 10.1017/s0954579405050091
|View full text |Cite
|
Sign up to set email alerts
|

Low salivary cortisol levels and externalizing behavior problems in youth

Abstract: Research linking basal cortisol levels with internalizing and externalizing behavior problems in youths has yielded inconsistent results. We hypothesize that the high moment to moment variation in adrenocortical activity requires an analytical strategy that separates variance in cortisol levels attributable to "stable traitlike" versus "state or situationally specific" sources. Early morning saliva samples were obtained from 724 youths~M age ϭ 13.5 years; range ϭ 6-16 years in Year 1! on 2 successive days 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
237
8
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(266 citation statements)
references
References 76 publications
20
237
8
1
Order By: Relevance
“…In addition to the month-tomonth mean variations in the CC group, we noted considerable individual variation from day to day and from month to month. This has been reported in other studies of cortisol sampling for young children, although there is evidence that somewhat greater day-to-day stability occurs among older children (Bartels et al, 2003;Shirtcliff et al, 2005).…”
Section: Groupsupporting
confidence: 65%
“…In addition to the month-tomonth mean variations in the CC group, we noted considerable individual variation from day to day and from month to month. This has been reported in other studies of cortisol sampling for young children, although there is evidence that somewhat greater day-to-day stability occurs among older children (Bartels et al, 2003;Shirtcliff et al, 2005).…”
Section: Groupsupporting
confidence: 65%
“…Single sample measures are moderately stable across 3 consecutive days: awake (α = .49), +30 min post-awakening (α = .77), afternoon (α = .58), and bedtime (α = .75;O'Connor et al, 2005). Similar findings have been reported across 2 consecutive days (Brosnan et al, 2009;Shirtcliff et al, 2005). Thus, while these results suggest some cortisol measures are moderately stable, a more rigorous examination of the stability of the diurnal cortisol profile in children and adolescents is necessary.…”
supporting
confidence: 72%
“…There are no findings regarding the stability of AUC TG or other single sample measures. (Brosnan et al, 2009;Shirtcliff et al, 2005). Thus, while these results suggest some cortisol measures are moderately stable, a more rigorous examination of the stability of the diurnal cortisol profile in children and adolescents is necessary.…”
Section: Cihr Author Manuscriptmentioning
confidence: 90%
“…However, 'These same flaws are common to a surprisingly high percentage of research in all areas of medicine, and are not necessarily more problematic in the AIDS area' [1]. These flaws are evident and have been acknowledged widely in the literature on the effectiveness of needle and syringe programmes (NSPs) [2,3]. In a recent editorial, Amundsen [4] relies on these limitations to question the status of NSPs as a 'superior tool' for HIV prevention and suggests that more emphasis be placed on testing and counselling to reduce risk behaviour in injecting drug users (IDUs).…”
Section: Response To Amundsenmentioning
confidence: 99%
“…One of these aspects concerns the question of whether the low morning cortisol levels (assessed 30 minutes after awakening) we found in adolescents who started using cannabis before the age of 13 years are associated with externalizing phenotypes. A number of studies have indeed found evidence [2] for hypoactivity of the HPA axis in children and adolescents with externalizing behaviours [3][4][5][6][7]. Another particularly interesting study in this regard is that of Vanyukov et al [8], who studied a high-risk sample of 78 10-12-year-old sons of fathers with addiction problems.…”
mentioning
confidence: 99%